Path Dependency in the Energy Industry: The Case of Long-term Oil-indexed Gas Import Contracts in Continental Europe - Buhanist, Peter (International Journal of Energy Economics and Policy, 2015)
This paper seeks to explain the persistence of a business model that was instrumental in creating pan-European natural gas markets but refused to retire when the markets outgrew it. Long-term oil-indexed agreements enabled the emergence of international gas markets in Europe since the early 1960s and they still govern gas imports to the EU. Yet, they failed to evolve with the changing business environment, resulting in the strategic costs for the companies. A politicized topic, research has thus far focused on national and regional levels, largely ignoring company level processes. This article contributes to the understanding of European gas markets by introducing a company level behavioral explanation of the endurance of an institutionalized but seemingly outdated business model. Path dependence is found to be a major contributing factor of the behavior of agents. Business leaders and governments alike will benefit from learning to identify and avoid path dependent behavior that leads to potentially sub-optimal outcomes. Keywords: Gas trade; Gazprom; Path dependence JEL classifications: F; M; Q